What do parents of children with autism expect from participation in research? A community survey about early autism studies. (January 2019) - Fletcher-Watson, Sue; Larsen, Kenneth; Salomone, Erica
Engagement with stakeholders is an essential part of the research process. This is particularly the case for early autism research with infant cohorts and their families, where a range of ethical issues are pertinent. Here, we report on a large survey of parents who have a child on the autism spectrum (n = 1040) which specifically probed attitudes to early autism research. The large majority of parents showed positive attitudes overall, and these were associated with greater access to services, higher service quality ratings and higher rates of intellectual disability among their children. Parents valued the scientific goals of research, but half of parents also reported that an intervention component would be an essential prerequisite for them to participate in research. If enrolled in a study, parents were positive about most commonly used measures though less favourably disposed towards brain scans for children. They valued direct contact with the research team and openness in data sharing. We interpret our findings in terms of lessons for the early autism research community and for stakeholder engagement projects.